Ant assemblages in successional stages of Scotch Broom stands - DAUBER, JENS; Simmering, D. (Osterreichische Gesellschaft fur Entomofaunistik, 2006)
Scotch Broom (Cytisus scoparius [L.] LINK) stands are important seminatural habitats in cultural landscapes of Ger-many. High structural diversity of broom stands is reflected by a high species diversity of the flora and fauna, giving them a high value for biodiversity conservation. The aim of this study was to assess the composition and structure of ant assemblages among successional stages of Scotch Broom stands, and compare these with assemblages in arable land and the climax forest habitat. We addressed, whether ant species richness in successional broom stands differ with respect to the dominant grass species, shrub cover and other structural variables describing vegetation. Furthermore, we studied whether ant species composition relates to plant species composition, and whether site productivity or structural vegetation properties are more important for ant species composition. We found that initial and climax stages of the succession constitute habitats which are very different from the "Scotch Broom stages" of succession. Ant species richness was not correlated to plant species richness but was best predicted by the two variables "moss cover" and "soil moisture". Path Analysis revealed that both site productivity and vegetation structure had an independent and significant effect on ant species composition. The estimate of the explanatory power of the "Productivity" path was twice the magnitude of "Structure". The successional dynamics within stands of Scotch Broom created complex habitat structures that provide diverse microhabitats for ants. The type of grassland vegetation was of little importance and there-fore, schemes to maintain these old fields as ant habitats do not necessarily need to manage for a particular plant species composition but for dynamic and structurally rich sites. Due to site specific differences in soil attributes, legacy of for-mer land use and Scotch Broom dynamics, single sites are of very individual character and harbour different ant as-semblages. This causes high beta diversity and thus high ant species richness in Scotch Broom stands at the landscape scale. Therefore, conservation strategies for Scotch Broom stands should focus on maintaining a high number of sites widely dispersed within the landscape.
PUBLISHED
Keywords: Succession; old field; Cytisus scoparius; conservation biology; assemblage similarity; site productivity; vegetation structure; temperate grasslands